TSG-6 Downregulates IFN-Alpha and TNF-Alpha Expression by Suppressing IRF7 Phosphorylation in Human Plasmacytoid Dendritic Cells - L. Kui; G. C. Chan; P. P. W. Lee (Mediators of Inflammation)
Proinflammatory cytokines such as TNF-α and type I interferons (IFN) are pathogenic signatures of systemic lupus erythematosus, and plasmacytoid dendritic cells (pDCs) play a major role by predominantly producing IFN-α. Given the rise of importance in identifying tumor necrosis stimulated gene 6 (TSG-6) as a key anti-inflammatory regulator, we investigate its function and its ability to counteract proinflammatory cytokine secretion by pDCs in vitro. CpG-A and R837 induced significant endogenous TSG-6 expression in the pDC cell-line GEN2.2. Following recombinant human TSG-6 treatment and CpG-A or R837 stimulation, significant reduction in IFN-α and TNF-α was observed in healthy donors’ pDCs, and the same phenomenon was confirmed in GEN2.2. By CD44 blocking assay, we deduced that the suppressive effect of TSG-6 is mediated by CD44, by reducing IRF-7 phosphorylation. Our findings suggest that TSG-6 and its downstream signalling pathway could potentially be targeted to modulate proinflammatory cytokine expression in pDCs.